En el reino de la ambivalencia. La Cuba de Alejandro de Humboldt - Oliver Lubrich (HiN - Alexander von Humboldt im Netz. Internationale Zeitschrift für Humboldt-Studien, 2001)
Article in Spanish, Abstracts in English and German.In the Realm of Ambivalence.The Question of Cuba in Alexander von Humboldt’s American TravelogueCuba has a special role in Alexander von Humboldt’s American travel narrative: Humboldt’s experience of colonial slave economy drives his optimistic philosophy, inspired by European Enlightenment, into a crisis, and brings to surface the inherent contradictions of his discourse. This phenomenon is particularly interesting from the perspective of literary criticism: Alexander von Humboldt conceives Cuba as a poetic space, where contradictions and ambivalences coexist. Already on the boat to the island from Venezuela he creates destablizing effects of sensual perceptions. He stages his landing in Havana as a moment of oppositional impressions. Within the symbolic topography of his geographic fantasy, Cuba functions as an imaginary in-between space. And Humboldt’s philosophical and aesthetic terminology undergoes a semantic recoding in Cuba: what was once used in a philosophical and aesthetic sense, now has become charged with an economic and political meaning.